Impact of Self Service Technology on Customer Behavioral Intention: Case of Intercity Railway Service in Sri Lanka (Global Journal of Management and Business Research, 2019)
The underperforming railway transportation in Sri Lanka is still running on ticket reservation techniques. Sri Lanka, the public transportation sector is yet to realizes the usefulness of self-service technologies. Since the majority of the industries moved forward with self-service technologies and, Sri Lankan customers are already familiar with these types of smart technologies, we expect customer behaviour toward railway self-service technologies will also become more positive. Existing processes are consisting of lots of non-value adding and waste activities. To solve these problems, researchers trying to explore the customer behavioural intention toward a railway self-service ticketing system and design a national framework for the Sri Lanka intercity railway. Through that Sri Lanka Railways can reduce issues related to the current process. For that researcher using exploratory research design and inductive approach and both quantitative and qualitative data gathering methodologies used to gather information. Purposive sampling method using to identify participants for the questionnaire.
Keywords: railway ticketing; smart self-service ticketing; process improvement; smart technologies; digital transformation